Conventional DMARD therapy (methotrexate-sulphasalazine) may decrease the requirement of biologics in routine practice of ankylosing spondylitis patients: A real-life experience - (:unkn) unknown (WILEY, 2012)
Aim The effect of disease-modifying antirheumatic drugs (DMARDs) in ankylosing spondylitis (AS) is still controversial. We aimed to evaluate the efficacy of sulphasalazine (SSZ) mono- or combination therapy with methotrexate (MTX) in AS patients naive to anti-tumor necrosis factor alpha (TNFa) agents. Methods Patients with AS (n = 87, male : female, 46 : 41) treated with SSZ (n = 61) or SSZ + MTX (n = 26) combination and a documented 6-month follow-up were evaluated retrospectively. Disease activity was assessed by the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), C-reactive protein and erythrocyte sedimentation rate. Requirement for anti-TNFa therapy was assessed after 6 months. Results Mean (SD) age was 43.0 (11.0) versus 40.2 (11.1) and disease duration was 11.0 (8.6) versus 8.2 (5.2) years, in the SSZ and SSZ + MTX groups, respectively. Initially, 59% (34/61) of the patients in SSZ monotherapy and 68% (17/26) in the combination arm had BASDAI > 4. At the end of the study, BASDAI scores decreased similarly in both groups (mono: 1.4 [76] versus combination: 0.7 [36] P = 0.2). BASDAI was > 4 in 32.8% (20/61) of patients in the SSZ monotherapy and in 44% (11/26) in the combination arm. Only 4 (6.6%) patients in the SSZ group and 2 (7.7%) in the ombination arm were switched to anti-TNFa therapies. Discussion A significant subset of our AS patients responded to SSZ mono or SSZ + MTX combination therapies at 6 months follow-up. Using BASDAI, the requirement for biological therapies decreased by 2124%. In AS patients, including those with axial involvement only, DMARD therapy may be a reasonable first alternative to anti-TNFa therapy and may delay the switch to biologic agents.
Keywords: ankylosing spondylitis; disease activity; therapy; DOUBLE-BLIND; DISEASE-ACTIVITY; EFFICACY; PLACEBO; UPDATE